Phenotypic variability of prenatally presenting Gaucher's disease. (4th July 2013) - Beaujot, Juliette; Joriot, Sylvie; Dieux, Anne; Vaast, Pascal; Franquet‐Ansart, Hélène; Valat, Anne‐Sylvie; Deruelle, Philippe; Holder‐Espinasse, Muriel; Devisme, Louise
<x xml:space="preserve">Abstract</x> What's already known about this topic? Recently, a new subgroup of Gaucher's disease type 2 with early manifestations during fetal life has been reported. What does this study add? This report illustrates the diversity of fetal malformations observed in this entity, also called perinatal lethal Gaucher's disease, and, because of phenotypic variability, the autopsy with histological examination is useful to discuss this diagnosis.